Organizational Creativity Management Model To Improve The Competitiveness of High Schools in Indonesia - Sundusiah, Sundusiah; Agus, H; Disman, H; Suryadi, Edi (Jurnal Ilmu Sosial Mamangan, 2025)
Recent years have witnessed a notable expansion in the number of educational facilities, reflecting a vibrant evolution within the realm of education. A heightened awareness of the importance of education is one of the factors that has facilitated the growth and development of a multitude of educational institutions. However, the primary criterion for evaluating the development of educational institutions is the quality of education they provide. This is particularly evident in the context of the proliferation of educational institutions in our environment. Educational institutions that have demonstrated robust growth are those that have developed competitive strategies by identifying and capitalizing on existing opportunities, while also pursuing continuous improvement. Achieving these goals requires the implementation of a multifaceted approach. Competitive advantage represents one such strategy, whereby institutions formulate plans to capitalize on opportunities and consumer interests by maximizing revenue from investments. This approach serves as a pivotal solution in navigating the competitive landscape of educational institutions.